2021
DOI: 10.3889/oamjms.2021.6025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Family Support in the Recovery of Corona Virus Disease-19 Patients

Abstract: BACKGROUND: Families have an important role in prevention for patients who are positive for coronavirus diseases (COVID)-19 with mild symptoms and without symptoms to recover. Support such as providing positive information, moral reinforcement, and special time given by the family is thought to strengthen mental health and can increase the immunity of the patient. AIM: The purpose of this study was to determine the role of family support in the recovery of COVID-19 patients. METHODS: Used was observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Similarly, a study in Indonesia revealed that good family support positively impacts the recovery of patients with COVID-19. 32 Likewise, a study in Amsterdam found that patients with COVID-19 perceived family support from their relatives as positive, allowing them to reduce anguish and anxiety. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study in Indonesia revealed that good family support positively impacts the recovery of patients with COVID-19. 32 Likewise, a study in Amsterdam found that patients with COVID-19 perceived family support from their relatives as positive, allowing them to reduce anguish and anxiety. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in Indonesia revealed that good family support positively impacts the recovery of patients with COVID-19. 32 Likewise, a study in Amsterdam found that patients with COVID-19 perceived family support from their relatives as positive, allowing them to reduce anguish and anxiety. 33 Lastly, the multivariate analysis found that people with COVID-19 who perceived high family support were 33.74 times (95% CI: 7266-156,739) more likely to have a high capacity for coping strategies (Table 4).…”
mentioning
confidence: 99%
“…Peñarrieta et al [48] showed that family support has a significant role in reinforcing the management of diseases in the persons with chronic diseases. Studies performed in China and Indonesia showed that during the COVID-19 pandemic, family support has an important and positive role in preserving the mental health and recovery from the disease [49,50]. Also, investigations showed the significant role of family support in promoting health and reducing the risk of illness, preventing disease onset, influencing health care and treatment decisions, helping members highly susceptible to stress, and care and recovery [51,52] 3.1.3.…”
Section: Study Overview and Prospectmentioning
confidence: 99%